The Effect Of Company Size, Profitability, Leverage, And Management Ownership Towards The Level Of Corporate Social Responsibility (CSR) Disclosure - Jacqueline Vania Wardhani; Luky Patricia Widianingsih; Frandy Karundeng (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
The Government has regulated CSR activities through Law No. 40 Year 2007 regarding Limited Liability Company. Mentioned that the company must perform and disclose CSR activities, especially companies that related to natural resources such as mining companies. The objective is to know the effect of company size, profitability, leverage, and management ownership on the level of CSR disclosure of mining companies listed on BEI during the period of 2014-2017. Using secondary data from annual report and financial report. The samples sum up to a total of ten companies with a four-year observation period, resulting in a total of 40 observational data. The method used in this research is multiple linear regression using SPSS 22.0 program. The result of the research shows that (1) firm size has positive effect on CSR disclosure level, (2) profitability and leverage has no effect on CSR disclosure level; (3) management ownership negatively affect CSR disclosure level. This finding contributes to the future research, companies, creditors, investors, and government.